A stochastic model of jaguar abundance in the Peruvian Amazon under climate variation scenarios. Issue 19 (21st September 2020) - Burrage, Kevin; Burrage, Pamela; Davis, Jacqueline; Bednarz, Tomasz; Kim, June; Vercelloni, Julie; Peterson, Erin E.; Mengersen, Kerrie
Abstract: The jaguar (Panthera onca) is the dominant predator in Central and South America, but is now considered near‐threatened. Estimating jaguar population size is difficult, due to uncertainty in the underlying dynamical processes as well as highly variable and sparse data. We develop a stochastic temporal model of jaguar abundance in the Peruvian Amazon, taking into account prey availability, under various climate change scenarios. The model is calibrated against existing data sets and an elicitation study in Pacaya Samiria. In order to account for uncertainty and variability, we construct a population of models over four key parameters, namely three scaling parameters for aquatic, small land, and large land animals and a hunting index. We then use this population of models to construct probabilistic evaluations of jaguar populations under various climate change scenarios characterized by increasingly severe flood and drought events and discuss the implications on jaguar numbers. Results imply that jaguar populations exhibit some robustness to extreme drought and flood, but that repeated exposure to these events over short periods can result in rapid decline. However, jaguar numbers could return to stability—albeit at lower numbers—if there are periods of benign climate patterns and other relevant factors are conducive. Abstract : We develop novel statistical methods to address urgent conservation problems characterized by high levels of uncertainty. We demonstrate these methods by forecasting the effects of severe climate events on jaguar populations in the Peruvian Amazon basin.